Application of Blockchain ​​Technology (Ethereum) in Building Dermatology Health Care System - Dinh, Thi Cam Ly (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Software Engineering; 2020 - 2025